Influência da implantação de bacia de detenção e da ocupação no amortecimento de hidrogramas e do transporte de material solúvel utilizando modelo reduzido - Quiles, Eliane Zaparoli (2019)
The management of water resources in urban areas is an issue that has been growing in relevance in the last decades due to the rising urbanization of the world. There are several environmental, social and economic impacts caused by an inadequate planning, management and maintenance of rainwater drainage systems. In addition to interfering in the quantitative aspect of water resources, urbanization also interferes with the qualitative aspect of water resources, as it increases the variety and quantity of pollutants and nutrients that reach the water bodies that drain urban areas. The objective of this project is to analyse the influence of a detention basin and occupancy density on the reduction of peak flow and the transport of soluble material on an impermeable surface, using a reduced physical model and an experimental design. The tests were performed spreading simulated rainfall on an impermeable surface of 100m2, altering the independent variables of the study, which are: the mass of soluble material applied to the surface, represented by sodium chloride, kept in an oven; the position of the material relative to the exudate; the occupancy density, represented by blocks of expanded polystyrene; and duration of simulated rainfall. A rotational central composite experimental design was used to optimize the experiments. Hydrographs, pollutographs, equations and response surfaces were obtained which showed that the holding basin was able to reduce peak flow, transport material and delay the peak time of the mass discharge of material. Eight dependent variables were studied and statistically related to the independent variables, it are: peak flow, volume of water drained, peak mass discharge, peak time of the polutogram, the initial time of the polutogram, the final time of the pollutogram, mass transported and percentage transported. It can be concluded that the detention basin was able to damp the flow peak by approximately 44%. In addition, the detention basin reduced the peak mass discharge by an average of 63%. For each dependent variable analyzed, one or several independent variables demonstrated a statistically significant relationship, some with better adjustments than others. It was possible to conclude that the design used was adequate for this work, and it was possible to obtain relevant statistical models for the study.